Phase equilibria in electrolyte systems - Pinho, Simão (2000)
The main objectives of this work are the study of solid-liquid equilibrium of salts in pure and mixed solvents, and of biomolecules, such as amino acids and peptides, in water. The correlation and prediction of properties for mixtures containing charged electric species, the electrolytes, is of great relevance for the chemical industry. A brief discussion about the whole interest of this work and the need of concentrating efforts to develop accurate models for electrolyte systems is initially focused. The fundamental concepts of electrolyte thermodynamics and industrial examples where electrolytes play an important role are given. The available different models to correlate and/or predict properties and phase equilibria for this kind of mixtures are reviewed and compared. An isothermal analytical method, which has been implemented to measure salt solubilities, is described in detail. The experimental solubilities obtained for NaCl, KCl, NaBr and KBr, in the pure solvents water, methanol, ethanol and in the mixed solvents water/methanol, water/ethanol and methanol/ethanol in the temperature range between 25 oC and 80 oC are given. The new experimental data is used together with additional information published by other authors, concerning solid-liquid equilibrium of salts in pure and mixed solvents and osmotic coefficients in pure solvents, in order to establish an extensive and reliable database. This is adopted for the development of consistent thermodynamic models. Two UNIQUAC based models are suggested: the UNIQUAC + Pitzer-Debye-Hückel model, and the UNIQUAC model with linear temperature dependent solvent/salt parameters. A new developed approach for correlating salt solubilities, based on the symmetric convention of normalization of the activity coefficients and on the mole fraction concentration scale on ionized basis is presented. In this way, it is possible the direct access to the salt solubility product in terms of its calorimetric properties such as the melting temperature, enthalpy of fusion and heat capacity change. The capabilities of these models for the correlation and prediction of solid-liquid equilibrium and other thermodynamic properties are discussed. The results indicate that this procedure and these models are satisfactory for solid-liquid equilibrium calculations. The work on weak electrolytes consists of the development of a new group-contribution method. This includes two terms: the UNIFAC model to account for the short-range interaction forces, and a Debye-Hückel expression for the long-range forces. New UNIFAC groups have been assigned to describe the amino acids and peptides studied, and the chemical equilibrium is taken into account simultaneously with the physical equilibrium. Using this approach, the temperature and pH effects on the solubilities of amino acids in aqueous solutions are taken into consideration. This model predicts very successfully the pH influence on the solubilities of amino acids and therefore may be used for engineering purposes.